Growth Performance of White Snapper (Lates calcarifer) With Different Stocking Density in Hapa at Hatchery Laboratory Tual State Fisheries Polytechnic - Sahusilawane, Helena Afia; Beruatjaan, Mariana Y; Erbabley, Nally Y G F; Metengun, Jakomina; Kilmanun, Juliana E (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2025)
Maluku are known as the national fish barn and the largest fishing centre in Indonesia. One type of fish caught in Maluku is white snapper (Lates calcarifer), which is in high demand in the market. Therefore, intensification of aquaculture is essential. Determining factors for successful aquaculture include the stocking density of fry in aquaculture containers. The objective of this study was to determine effect of the stocking density on growth performance of white snapper cultivated in hapa. This observation took place over a month at the Hatchery Laboratory of the Aquaculture Technology Study Programme at the Tual State Fisheries Polytechnic. This study was used a completely randomised factorial design consisting of stocking densities of 10 fish/hapa, 15 fish/hapa, and 20 fish per hapa. Each treatment was repeated three times. The white snapper fish were obtained from the Tual Marine Cultivation Centre with a uniform size of 5-6 cm. The fish were cultivated in 40x40x40 cm hapa in fibre tanks using the RAS method and were fed commercial feed ad libitum. The growth parameters measured were length, weight, and growth rate of the fish. The data were analysed using one-way analysis of variance and followed by the DMRT test in the SPSS 22.0 program. The results showed that stocking density had a significant effect on the growth of white snapper during cultivation. The stocking density treatment of 10 fish/hapa had higher length and weight measurements each week of observation compared to other treatments. Thus, the lower the stocking density of white snapper in the hapa, the higher its growth. To achieve optimal growth in aquaculture, it is recommended to use a low stocking density of fish.